Uso de levedura seca na alimentação de cabras saanen, primíparas e multíparas, em lactação - Gomes, Ludmila Couto (2011)
There were used 24 Saanen goats, 15 multiparous and nine primiparous, distributed in a completely randomized design in factorial arrangement (3 diets x 2 orders of parturition). The treatments were soybean meal (SB), soybean + dry yeast (SBDY) or dry yeast (DY) as a protein source in diets, where the corn silage has participated in 40% of the mixture. The objectives were to determine the intake and digestibility of dry matter and nutrients, to estimate the energy value of feeds, to evaluate the intake of dry matter, lactation curves and body weight and to evaluate the yield and milk quality of Saanen goats. The lactation was divided into three stages: post-partum (up to 60 days of lactation), post-peak (61 to 130 days) and late lactation (131 to 200 days). The intake and digestibility of dry matter and nutrients and total digestible nutrients (TDN) were determined in three phases and the fecal excretion was estimated using indigestible neutral detergent fiber as internal marker. For analysis of the lactation curves was assumed the nonlinear model of Wood. The controls of intake and milk production were daily. Diets did not affect dry matter intake (DMI). Multiparous goats had higher DMI and nutrients compared to primiparous. The digestibility of dry matter and TDN were higher for primiparous in the post-partum. In the post-peak and in the end of lactation no difference was observed in digestibility of DM and nutrients for orders of parturition. The TDN was similar to the diets. The goats fed with DY diet had lower urea nitrogen in blood. For primiparous goats receiving diets SBDY and DY the milk initial production increased, however, for multiparous this production decreased. The dry yeast decreased the rate of production increase to peak for primiparous, but to the multiparous were observed the reverse. For primiparous goats the diet SBDY decreased the rate of decline in production after the peak, although for multiparous the dry yeast in the diet increased the rate of decline in production after peak. The highest average daily production was observed for primiparous receiving the SB diet, while for the multiparous, higher average daily production was the diet with DY. The diets did not affect the DMI in the pre-partum, post-partum and post-peak. However, goats consuming DY diet had lower DMI in the end of lactation. Among orders of parturition the higher DMI were observed to the multiparous in the pre-partum, post-partum and post-peak. Milk production was not changed by the diets. Multiparous goats produced more milk at all stages of production. The efficiency of milk production was not affected by diet or orders of parturition. The percentage of protein and lactose, density and acidity in milk were not influenced by diets or orders of parturition. However, the percentages of fat and total solids in the post-partum period were higher for primiparous goats. The somatic cell count was lower for the multiparous in the post-peak. The use of dry yeast in substitution of soybean meal in diets for feeding Saanen goats primiparous and multiparous in lactation is a good alternative to maintain the nutritional value of diets and the milk production. However, for primiparous goats, the dry yeast changes the parameters of lactation curve.